Cenas festivas da/na cidade de Belo Horizonte: 1897-1922 - Wanessa Pires Lott (2009)
Belo Horizonte is inaugurated in 1897 to be the capital of Minas Gerais and a symbol of the Republican regime in Brazil. Despite being built for the values of secular modernity, of the epiphany, by the way of celebration of its people, values of tradition. In this sense, the city does not separate completely the values of tradition and religion and do not aggregate the values of modernity and secularism. Belo Horizonte places in the state threshold for the separation and the aggregation of values. The dissertation deals with festive scenes of /in the city of Belo Horizonte in the opening period (12 December 1897) to the centenary celebration of the Independence of Brazil (07 September 1922). Want to understand the values of the epiphany by religious and civic celebrations. The historiographic, ethnographic field is bounded by the newspapers of the Digital Collection Linhares theoretical and is based on history and anthropology.